ACADEMIC WRITING IN THE HISTORICAL AND LINGUSTIC CONTEXT: AN EXAMPLE OF GERMAN LANGUAGE - Fairuza F. Nasibullina; Artem N. Bezrukov (Высшее образование в России)
The paper describes linguistic approach to the development of academic writing in the world. Historical analysis is carried out for changes of languages used for academic writing, their interrelation and succession. German language is selected to study modern issues of scientific writing and excessive use of English words. Different types of linguistic adoptions are discussed, provided examples reveal their influence on grammar, lexicology and punctuation of academic German language.